Formula of macrobrachium nipponense feed and method for preparing macrobrachium nipponense compound feed from macrobrachium nipponense feed - HU PAN; YIN YANQIANG; HUANG XUXIONG (2011)
The invention relates to a formula of a macrobrachium nipponense feed and a method for preparing a macrobrachium nipponense compound feed from the macrobrachium nipponense feed. The formula of the macrobrachium nipponense feed consists of fish meal, fermented soybean meal, peanut meal, blood powder, yeast, flour, multi-vitamin, multi-mineral, shrimp bran, soybean oil, fish oil, phospholipid oil, squid liver powder and yeast extract. The method for preparing the macrobrachium nipponense compound feed from the macrobrachium nipponense feed comprises the following steps of: weighing according tothe feed formula, stirring and mixing in a stirrer, introducing steam, preparing particles with the particle size of 1 to 1.6mm, dehydrating, cooling, and reducing the temperature of the particles toroom temperature to obtain the macrobrachium nipponense compound feed. The macrobrachium nipponense compound feed is used for feeding macrobrachium nipponense, contributes to meeting the nutritional requirements of the macrobr